Etude d’éolienne à vitesse variable basée sur la machine asynchrone à double alimentation ( MADA ) - GRINE MOURAD (My University, 2011)
The work done in this thesis represents a comprehensive study on the production of electricity by wind turbines with variable speed based on the double-fed asynchronous machine (DFIG). The fundamental concepts of the production line of electric energy and the various associations-electric machines converters can be coupled to a wind turbine. In our study we take the double-fed asynchronous machine (DFIG) or it is fed by a converter to the rotor while the stator is connected to the network (functioning as a generator for an application type wind) associated with the modeling power control of DFIG, also with the realization of a global chain of our conversion is in MATLAB or so with the results of simulations according to the wind speed (for wind speed for optimal operation). Therefore, we end with conclusions on this conversion.